A story superiority effect for disgust, fear, embarrassment, and pride. (27th March 2013) - Nelson, Nicole L.; Hudspeth, Kate; Russell, James A.
Abstract : Past studies found that, for preschoolers, a story specifying a situational cause and behavioural consequence is a better cue to fear and disgust than is the facial expression of those two emotions, but the facial expressions used were static. Two studies (Study 1: N  = 68, 36–68 months; Study 2: N  = 72, 49–90 months) tested whether this effect could be reversed when the expressions were dynamic and included facial, postural, and vocal cues. Children freely labelled emotions in three conditions: story, still face, and dynamic expression. Story remained a better cue than still face or dynamic expression for fear and disgust and also for the later emerging emotions of embarrassment and pride.